2002
DOI: 10.1046/j.1432-1033.2002.03161.x
|View full text |Cite
|
Sign up to set email alerts
|

NblA from Anabaena sp. PCC 7120 is a mostly α‐helical protein undergoing reversible trimerization in solution

Abstract: The nblA family of genes encodes for small proteins necessary for the ordered degradation of phycobilisomes under certain stress conditions, a process known as chlorosis. Genes homologous to nblA seem to occur in all phycobilisome‐containing organisms. However, to date, no molecular mechanism is known for the action of NblA, nor have the gene products been characterized to understand the physical properties of the molecule and thus help elucidate the mechanism on a structural basis. In this study we report on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…One of the first questions that arose during structure determination concerned the native oligomerization state of NblA. Previous characterization of NblA by analytical ultracentrifugation indicated an association reaction of folded monomers to form trimers (10). Furthermore, analytical size exclusion chromatography yielded apparent molecular masses of 18.3-20.6 kDa, indicating a dimer or trimer (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the first questions that arose during structure determination concerned the native oligomerization state of NblA. Previous characterization of NblA by analytical ultracentrifugation indicated an association reaction of folded monomers to form trimers (10). Furthermore, analytical size exclusion chromatography yielded apparent molecular masses of 18.3-20.6 kDa, indicating a dimer or trimer (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…NblA Overexpression and Purification-The chromosomal gene asr4517 coding for NblA (kazusa.or.jp/cyano/Anabaena/index.html) from Anabaena 7120 was cloned into plasmid pET11a (Novagen) as described earlier (10). A selenomethionine (Mse) NblA derivative was produced in Escherichia coli B834 (DE3), which is auxotrophic for methionine, according to a protocol from Budisa et al (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it can be argued that the NblA of each species may function through a completely different set of interactions, it is also possible that the molecular details on how the NblA functions are quite different from those previously proposed (20). In this study, we present the structures of NblA from the thermophilic cyanobacterium Thermosynechococcus vulcanus (TvNblA) and the mesophilic cyanobacterium S. elongatus (SeNblA).…”
mentioning
confidence: 93%
“…The structure revealed that the monomer consists of a helix-loop-helix motif which dimerizes to form an open four-helical bundle. Although not stated specifically that the NblA dimers were present in solution before crystallization (in fact an earlier report on the NblA from the same organism suggested a trimeric form in solution (20)), it is implicitly stated by these authors that the dimer is the basic structural unit of the NblA. On the basis of short stretches of sequence homology, in vitro analysis of site-directed mutations and in vitro binding assays, these authors also proposed that the NblA protein interacts with the PBPs via the C terminus.…”
mentioning
confidence: 95%